Assessment of nanomaterials in enhancing the thermophysical properties of phase change materials for thermal management - Arshad, Adeel (2021)
The rapidly growing and innovation of electronics devices with advanced smart and faster features raises a thermal challenge for an effective and clean cooling technology to ensure the reliable and safe operating temperature range of integrated circuits. A novel zero-noise, zero-power and zero-emission passive thermal management technology based on phase-change thermal energy storage systems has turned out a revolutionary advancement in smart cooling technologies. Such a cleaner, sustainable and reliable thermal management technology is integrated with such materials that have an intrinsic potential of absorbing/releasing the thermal energy during phase--transformation, called phase change materials (PCMs). The PCM can absorb/release the high energy storage density while the melting/solidification process with a stable phase-transition temperature range. Meanwhile, it has some issues mainly lower thermal conductivity, subcooling, less thermal stability, etc. The present research explores the development and evaluation of new smart and novel energy storage materials in form of nanocomposite phase change materials (NCPCMs) with higher thermal conductivity, optimum enthalpy of fusion and higher heat transfer improvement with higher stability and lower subcooling for constant and transient thermal solutions. The comprehensive research literature provides the background of existing literature of nanomaterials, PCMs its classifications, NCPCMs and its classifications, stability of NCPCMs, issues and challenges of NCPCMs. To this extent, the novel mono and hybrid NCPCMs of different metallic-oxide and carbon-additives nanomaterials are prepared using two-step method and characterized to evaluate the thermophysical properties, stability and to study the heat transfer and phase-transition phenomenon during the melting/cooling process. The two different commercially available PCMs, RT-28HC and RT-35HC with phase-transition temperatures of 28 $^{°}$C and 34-36 $^{°}$C, respectively, are chosen, which are the most suitable for passive thermal management of smart electronic devices, photovoltaic modules and Li-ion batteries, working under the safe and reliable operating temperature range of 30-40 $^{°}$C. Nanomaterials such as metallic-oxide (TiO2, Al2O3, CuO) and carbon-additives (MWCNTs, GNPs, GO, rGO) are dispersed as thermal conductive materials (TCMs) to enhance the physical, chemical and thermal properties and heat transfer enhancement under natural convective conditions. Initially, the mass concentration of TiO$_{2}$ nanomaterials is varied from 0.0 wt.% to 2.0 wt.% in the case of mono NCPCMs. After considering the optimum mass concentration of 1.0 wt.% of nanomaterials, the comparisons are carried out of mono and hybrid nanomaterials by keeping the mass concentration ratio of 75%/25% of the total mass concentration. Secondly, the comparison of mono and hybrid NCPCMs are carried using TiO2, Al2O3 and CuO based metallic-oxide nanomaterials and the thermal performance is examined by filling in a mini heat sink. Thirdly, the carbon-additives such as MWCNTs, GNPs, GO, rGO are dispersed in RT-35HC and mono and hybrid NCPCMs are synthesized and evaluated the thermophysical properties. Fourthly, the comparison of carbon-additives (GNPs and MWCNTs) and metallic--oxide (Al2O3 and CuO) based nano and hybrid NCPCMs is carried out to explore the best type and combination of mono and hybrid nanomaterials between the metallic-oxide and carbon--additives. The detailed experimentation is carried out using various characterization techniques such as Environmental Scanning Electron Microscopy (ESEM) and Energy-dispersive X-ray Spectroscopy (EDX), Fourier-Transform Infrared Spectroscopy (FT--IR), X-ray Diffraction (XRD), Thermogravimetric analysis (TGA) and derivative thermogravimetry (DTG), Differential Scanning Calorimeter (DSC), and Thermal Conductivity Analyser. In addition, the melting/cooling phenomenon and heat transfer performance were studied using Infrared Thermography (IRT) tests. Finally, a CuO coated metal-foam mini heat sink is designed to pour the pure PCMs and NCPCMs to evaluate the phase--change thermal cooling performance at different power levels, to mimic the heat generation inside the electronic devices. The summarized results revealed that the carbon-additives based NCPCMs had better stability, more enhanced thermophysical and uniform melting/cooling phenomenon with low subcooling issues. A better and enhanced physical, chemical and thermal stability was achieved comparing all mono and hybrid NCPCMs of all cases with the help of surfactant. Moreover, the best stability was obtained with GNPs and MWCNTs based hybrid NCPCMs compared to all other mono and hybrid NCPCMs. The surface morphological, structural investigation and transmission spectrum disclosed the presence of GNPs, MWCNTs, GO, rGO, TiO2, $γ-$Al2O3 and CuO nanomaterials in NCPCMs. The enhanced thermal conductivity results were obtained of hybrid NCPCMs and the maximum thermal conductivity of 0.443 W/m.K and thermal conductivity enhancement of 107.6% was obtained for GNPs+MWCNTs dispersed hybrid nanomaterials compared to the RT-35HC. The optimum values of latent-heats of melting/solidification of 230.82/234.19 J/g, the 13.75% enhancement in specific heat capacity, the less degree of subcooling of 3.47 $^{°}$C and 0.22% deviation in peak melting temperature were observed for GNPs+MWCNTs dispersed hybrid NCPCMs. The enhancement in specific heat capacity is based on three modes: (i) higher specific heat of nanomaterials, (ii) interfacial interactional layers between solid-liquid and (iii) semi-solid liquid layers of molecules adhering to the surface of nanomaterials. The highest thermal conductivity enhancement was due to the 3D structural matrix consisted of 1D (MWCNTs) and 2D (GO/rGO/GNPs) nanomaterials structural arrangement. This 3D matrix of hybrid NCPCMs forms the 3D path for which the phonon transmission and lattice vibration transport the heat effectively in all directions of the PCM. The reduction in heat sink base temperature was achieved 8.23% with Al2O3+CuO based hybrid NCPCMs and 9.7% and 8.72% for 1.0 and 0.5 filling thickness ratio of metal--foam without PCM and with PCM, respectively, which proposed the most preferable, efficient and reliable best thermal performance for passive cooling of electronics devices.